The Impact of Xerosis Cutis Severity on Quality of Life of Elderly - Frizka Eliza; Evy Ervianti; Damayanti (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Xerosis cutis occurs more frequently in elderly. This disease is associated with reduced quality of life. This study aimed to determine the impact of xerosis cutis severity on elderly patients' quality of life. Methods: The goal of this cross-sectional observational analytical study was to analyze the impact of xerosis cutis severity on the quality of life of elderly patients. The study was conducted at the outpatient unit clinic of Dermatovenereology Department, Dr. Soetomo General Hospital, Surabaya, Indonesia. This study included a total of 36 elderly patients. We assessed the severity of Xerosis cutis using the Xerosimeter score, and evaluated the quality of life using the Dermatology Life Quality Index (DLQI). Result: The majority of elderly patients with xerosis cutis had moderate severity with 22 patients (61.10%) and reported a moderate impact on quality of life with 17 patients (47.20%). The severity of xerosis cutis was also significantly correlated with quality of life (P<0.000). Conclusion: There is a significant, directly proportional relationship between the severity of xerosis cutis and quality of life, with the severity having a greater impact on quality of life.